Предмет: Алгебра,
автор: Аноним
Решите уравнения, пожалуйста.
x-2-(3+(7-2x)) = -6
5-x/2-x/4=x+x/3
Ответы
Автор ответа:
0
x-2-(3+(7-2x))=-6. 5-x/2-x/4=x+x/3
x-2-(3+7-2x)=-6. 5=x/2+x/4+x+x/3
x-2-3-7+2x=-6. 5=(6x+3x+12x+4x)/12
3x-12=-6. 5=25x/12
3x=-6+12. 25x=5×12
3x=6. 25x=60
x=6÷3. x=60÷25
x=3. x=2.4
x-2-(3+7-2x)=-6. 5=x/2+x/4+x+x/3
x-2-3-7+2x=-6. 5=(6x+3x+12x+4x)/12
3x-12=-6. 5=25x/12
3x=-6+12. 25x=5×12
3x=6. 25x=60
x=6÷3. x=60÷25
x=3. x=2.4
Похожие вопросы
Предмет: Русский язык,
автор: gaspar
Предмет: Информатика,
автор: nikitaloshka007
Предмет: Химия,
автор: dogs34426
Предмет: Математика,
автор: Олечка1023